The Coral Holobiont: A Brief Overview of Corals and Their Microbiome: SL520/SS733, 7/2024 - Schul, Monica D.; Smyth, Ashley R.; Patterson, Joshua T.; Zangroniz, Ana N.; Krueger, Shelly L.; Meyer, Julie (EDIS, 2024)
<!--StartFragment -->Caribbean and tropical western Atlantic reefs have declined drastically since the 1970s. In some locales like the Florida Keys, the decline of branching corals approached 98%. These declines are widely attributed to recurring stressors such as high ocean temperatures and disease. The preservation and restoration of reefs is imperative as coral reefs support 25% of the world's known marine species and create billions of dollars in economic value. However, current restoration efforts have low success rates, so researchers are looking to better understand how stony corals respond to and overcome these stressors. Pioneering efforts to elucidate the role of the coral microbiome have shown that microbes are an important component for stony coral health, nutrition, and disease defense. This publication is for various natural resource professionals who want information on corals, microbiomes, and how coral microbial ecology research is pushing our knowledge of corals and restoration forward. <!--EndFragment -->